2018
DOI: 10.3390/hydrology5040069
|View full text |Cite
|
Sign up to set email alerts
|

Mid-Century Daily Discharge Scenarios Based on Climate and Land Use Change in Ouémé River Basin at Bétérou Outlet

Abstract: This study evaluates the impacts of land use and climate changes on daily discharge in Ouémé river basin at Bétérou outlet. Observed rainfall and temperature over 2002–2008 and land use data of 2003 and 2007 were used. Corrected rainfall and temperature data, under RCP4.5 and RCP8.5 scenarios from regional climate model REMO were considered. Two land use scenarios from RIVERTWIN project were used. The first one, Land Use A (LUA), is characterized by stronger economic development, controlled urbanization, imple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
3
1
Order By: Relevance
“…The fit here is not as close as that reported by Emmanuel et. al., (2018) using the LISFLOD model (NSE=0.92 for calibration Tab.…”
Section: Evaluation Of the Model's Performancecontrasting
confidence: 95%
See 2 more Smart Citations
“…The fit here is not as close as that reported by Emmanuel et. al., (2018) using the LISFLOD model (NSE=0.92 for calibration Tab.…”
Section: Evaluation Of the Model's Performancecontrasting
confidence: 95%
“…The surface runoff potential of the catchment was moderate; however, substantial sub-surface water components suggest that sub-surface water development is viable as an alternative potential water resource for the basin. Although the surface runoff is moderate, Emmanuel et at., (2018) has noted that the Oueme River at the Beterou outlet will experience increased discharges for all the time horizons until 2050 and for all the combined climate and land use change scenarios. This information on the future of water resources in the basin is an invitation to water resource managers to plan for design and mitigation strategies to cope with the negative effects of increased discharges.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, climate models hold some biases that need to be corrected before any impact study. Numerous bias correction methods exist and are applied around the world [16][17][18][19][20][21][22], including delta change, linear scaling, distribution mapping, empirical and adjusted quantile mapping [18,23,24]. M'Po et al [18] showed that empirical quantile mapping (EQM) was the best among other bias correction methods over Ouémé catchment.…”
Section: Introductionmentioning
confidence: 99%